Colon Cancer: Overview on Improved Therapeutic Potential of Plant-Based Compounds Using Nanotechnology - Manuel López-Cabanillas Lomelí; Alexandra Tijerina-Sáenz; David Gilberto García-Hernández; Marcelo Hernández-Salazar; Rogelio Salas García; José Luis González-Llerena; María Julia Verde-Star; Anthonny Cordero-Díaz; Michel Stéphane Heya (Scientia Pharmaceutica)
Colon cancer (CC) is the third most frequent neoplasm, with a considerably high mortality rate. Due to the side effects of conventional forms of CC treatment (surgery, chemotherapy, and radiotherapy), several studies have focused on the use of medicinal plant derivatives to provide a green therapy for CC; although phytochemicals have shown promising results against CC, translating the results obtained in vitro and in vivo to the clinical setting remains a challenge. Indeed, like other orally applied medicines, medicinal plant derivatives have to cross different physiological barriers to reach the CC microenvironment, which considerably limits their dose-dependent therapeutic efficacy. On the other hand, phytocompounds are not free from biopharmaceutical drawbacks, so novel strategies using nanoparticles (NPs) have been proposed to overcome the physiological barriers of the body and provide controlled release of actives of interest. Accordingly, the current review provides an overview and discussion on the predisposing factors to CC and conventional treatment, the use of medicinal plants in CC treatment, and the advantages provided by NPs in the treatment of CC.